Expression, purification and glycoprotein characterization of a recombinant antibody generated from two expression systems - Banzon, Virryan B (2003)
In the recent years, recombinant glycoproteins have been widely used for therapy of various diseases. There is an increasing awareness on the importance of the carbohydrate portion of the glycoprotein due to the discoveries that these sugar residues are essential to the regulation of bioactivity, pharmacokinetics, immunogenicity, stability and therapeutic efficacy of the glycoprotein. In this study, a recombinant antitumor antibody against carcinogenic antigen (CEA) was generated using the Pichia pastoris yeast and baculovirus-mediated expression system (BEVS)...The results of the analysis show that the sugars attached to the BEVS-generated antibody consists mainly of oligomannosidic glycans.
"December 2003."
Thesis (M.S. Molecular Biology & Biotechnology) -- University of the Philippines Diliman.
Keywords: Recombinant antibodies; Recombinant baculoviruses; Glycoproteins